Solid mining waste from the mineral flotation process in the Santa-Áncash river basin - Romero, Alfonso (2008)
In Peru, work has been carried out in the area of ​​solid mining waste from the mineral flotation process since 2000, where the Ministry of Energy and Mines begins to carry out the inventory of mining environmental liabilities related to abandoned mining activities where it involves acidic waters, dumps, manholes and mining tailings, respectively; coming to the end to prepare the law 28271, law of regulation of the environmental liabilities of the mining activity, promulgated on July 2, 2004. In the Santa river basin the inventory of 153 mining environmental liabilities has been carried out, reaching the conclusion the urgency of conducting research studies to control the alarming contamination of the physical environment in this basin. At the end of the project, it establishes the preliminary technical parameters at the pilot level in relation to the granulometric and mineralogical characterization of the Ticapampa mining tailings, recommending that it be used as primary and aggregate material in the construction of pavements and the design of blocks. Preliminary tests of processes have been carried out to establish the physical, chemical, mechanical and mineralogical parameters to establish the characterization methodology of the abandoned mining tailings of Ticapampa, where the existence of useful elements is also seen, this characterization will define the tailings as raw material or input for another use and as such will allow to prevent, control, mitigate, remediate the affected areas and eliminate solid mining waste. By reusing these solid wastes, in the current geographical location an environmental quality physical environment will be provided, without alterations to the food chain of the human life cycle in areas where these liabilities are found. To mention an example, in Peru alone, there are approximately more than a trillion cubic meters of these solid wastes, the same ones that have affected the physical environment of the Peruvian territory for decades in an alarming way.